Antimicrobial sensitivity pattern of bacterial isolates causing meningitis - Sultana, Nahid; Husain, Md Anwar; Mazed, Md Abdul; Akter, Nasima; Sultan, Md Tipu; Hoque, Md Ehsanul (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i1.3849 Journal of Chittagong Medical College Teachers' Association 2008: 19(1):28-32